Dialogic Strategies and Social Media Integration: A Systematic Review of Digital Dialogue in Modern Communication - Shanmugam, Thinakaridevi; Abdullah, Zulhamri; Mohd Hasan, Nurul Ain; Sern, Tham Jen (Jurnal The Messenger, 2025)
Purpose: This study aimed to systematically examine the evolution of dialogic communication across major social media platforms from 2015 to 2024, including Facebook, Twitter, Instagram, YouTube, LinkedIn, TikTok, and WeChat, identifying key trends in theories, methodologies, and technological influences across interdisciplinary research fields. These platforms were chosen because of research relevance and features that support two-way interaction, making them suitable for analysing dialogic communication.   Methods: A systematic literature review was conducted on 199 peer-reviewed journal articles published in the Scopus database focus on studies on dialogic communication and social media. Articles were analyzed according to theoretical frameworks, research methodologies, social media platforms, and interdisciplinary contributions.   Findings: The results showed that Dialogic Communication Theory continues to dominate but is increasingly integrated with complementary frameworks such as Social Presence Theory, Uses and Gratifications Theory, and Algorithmic Engagement Models. Quantitative methods, especially content analysis and survey research, remain prevalent, though computational and mixed methods are gaining prominence. Futher findings revealed that AI-driven tools, chatbots, and interactive media features significantly shape digital engagement, offering new opportunities for audience interaction while presenting ethical challenges regarding authenticity and transparency.   Originality: This study offers research novelty by providing the first interdisciplinary synthesis of dialogic communication studies that integrates theoretical trends, methodological developments, and platform evolution. It also introduces a new perspective on how AI technologies and platform affordances reshape dialogic communication, highlighting emerging challenges and opportunities for ethical, transparent, and adaptive digital engagement. This integrated approach has not been comprehensively addressed in prior reviews.